A CRITICAL ANALYSIS OF CONTEXTUALIZED PUBLIC ART IN THE URBAN BRANDING OF INDIAN HERITAGE CITIES - Kirtane, Kaustubh Ashok; Kaushik, Hemant (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In the context of rapid urbanization and the global competition for tourism, Indian cities are increasingly adopting place branding strategies to cultivate distinct identities. However, a pervasive trend has emerged involving the uncritical replication of Western tropes, specifically the generic "I Love [City Name]" installations derived from Milton Glaser’s iconic New York campaign. This study critiques the "selfie point" phenomenon as a superficial place-marketing tactic that risks homogenizing urban landscapes and eroding local cultural distinctiveness. Adopting a qualitative case study approach, this research contrasts these derivative interventions with the context-specific public art ecosystem of Ujjain, Madhya Pradesh—a city of profound historical and spiritual significance. Through field observation, photographic documentation, and content analysis of visual narratives, the study examines how Ujjain leverages its "historicity"—spanning the Mahajanapada era to its status as a Kumbh Mela pilgrimage site—to create experience zones that function as authentic brand touchpoints. The research identifies a dichotomy between decentralized, ad-hoc generic installations and curated, narrative-driven public art that communicates specific cultural themes, such as the Samudramanthan mythology and the literary legacy of Kalidasa. Findings suggest that while generic installations suffer from spatial redundancy and lack emotional resonance, contextually grounded art effectively bridges the gap between heritage conservation and modern city branding. The paper concludes by arguing for a strategic shift in Indian urban governance: moving from mimetic ornamentation to the development of "narrative infrastructure" that aligns with theoretical frameworks of place identity, thereby fostering sustainable tourism and civic pride.